Bibliometric analysis of rumor detection via web of science from 1989 to 2021. (7th September 2022) - Rani, Neetu; Bhardwaj, Amit Kumar; Das, Prasenjit; Sharma, Anju
Summary: Through the enhancement of numerous social media sites, the rumor spread more rapidly among society and influences people in a very negative way. Nowadays, more attention is given by researchers to mitigating the threats produced by rumors. Bibliometric analysis is a prevalent and rigorous technique for discovering and investigating large volumes of systematic data. It assists us to identify the important aspects of that particular field. Motivated by earlier research we used this approach for our present study. The present study shows bibliometric analysis through VOSviewer software of 2935 records related to rumor dissemination by collecting the data from the web of science from 1989 to 2021. The bibliometric results have shown publication trends, main journals, most cited articles, most productive country, prominent authors, and institutions. Further net map analysis illustrates the growth of rumor detection in past, present, and future as well. Bibliometric and network analysis results from this research will significantly facilitate understanding the progress and trends in rumor detection.